2014
DOI: 10.1371/journal.pone.0089516
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol Add-On Therapy in Patients with Mild Dementia Receiving Donepezil: A Retrospective Study

Abstract: GoalCombinatorial therapy directed at both vascular and neurodegenerative aspects of dementia may offer a promising strategy for treatment of dementia, which often has a multifactorial basis in the elderly. We investigated whether the phosphodiesterase III inhibitor cilostazol, which is often used in the prevention of stroke and peripheral artery disease, may delay cognitive decline in the elderly receiving donepezil.MethodsMedical records were retrospectively surveyed to identify patients who had received don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 18 publications
1
53
1
Order By: Relevance
“…for the prevention of stroke or peripheral artery disease) reported that average daily doses above 100 mg for at least 6 months improved MMSE scores in MCI patients [38] and mild AD patients as add-on to 10 mg donepezil per day [39]. The same research group at the National Cerebral and Cardiovascular Center Hospital (Osaka, Japan) has started a new study investigating the effects on MMSE scores of cilostazol 50 mg twice a day for 96 weeks in patients with MCI (ClinicalTrials.gov identifier: NCT02491268).…”
Section: Phosphodiesterasementioning
confidence: 99%
“…for the prevention of stroke or peripheral artery disease) reported that average daily doses above 100 mg for at least 6 months improved MMSE scores in MCI patients [38] and mild AD patients as add-on to 10 mg donepezil per day [39]. The same research group at the National Cerebral and Cardiovascular Center Hospital (Osaka, Japan) has started a new study investigating the effects on MMSE scores of cilostazol 50 mg twice a day for 96 weeks in patients with MCI (ClinicalTrials.gov identifier: NCT02491268).…”
Section: Phosphodiesterasementioning
confidence: 99%
“…In the present study, we focused on the interaction of donepezil and cilostazol at efflux transporters as a potential explanation of the clinically reported cardiotoxicity of donepezil when coadministered with cilostazol (Tanaka et al, 2009;Shinozaki, 2012;Igeta et al, 2013). This is an important issue because simultaneous use of donepezil and cilostazol has been proposed to improve the pharmacologic outcome (Lee et al, 2007;Ihara et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism of the putative drug-drug interaction (DDI) has not yet been clarified, even though donepezil is often administered with other drugs, as it is frequently prescribed for elderly people. On the other hand, it has been proposed that coadministration of donepezil with cilostazol is more effective in patients with mild dementia (Ihara et al, 2014), and this has been supported by findings in an animal model (Lee et al, 2007). Accordingly, it is important to examine whether interaction of donepezil with cilostazol might occur, and if it does, whether it might have clinical relevance.…”
Section: Introductionmentioning
confidence: 98%
“…Cilostazol, an antiplatelet agent with pleiotropic effects based on phosphodiesterase-3-dependent mechanisms was studied for its use in management of AD [90] . A retrospective analysis of cilostazol as an addon therapy in patients with mild dementia receiving donepezil shown to suppress the cognitive decline [90,91] .…”
Section: Combination Therapy For Admentioning
confidence: 99%
“…A retrospective analysis of cilostazol as an addon therapy in patients with mild dementia receiving donepezil shown to suppress the cognitive decline [90,91] . Prospective randomized controlled trials (RCT) are required to validate these results.…”
Section: Combination Therapy For Admentioning
confidence: 99%